2020
DOI: 10.3126/bjhs.v5i3.33703
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Pruritus and associated factors in Chronic Dialysis Patients: An Observational Study in Western Nepal

Abstract: Introduction: Pruritus is one of the well-recognized major skin derangements in patients with advanced renal failure and are usually  without visible skin lesions. Only few studies have addressed this issue in Nepalese population. Objective:.The present study aims to identify the prevalence and associated factors of uremic pruritus in chronic dialysis patients in western Nepal. Methodology:A prospective observational study was conducted to include all chronic dialysis patients with uremic pruritus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Based on the results of research conducted by Kumar [11], who identified the relationship between male sex and pruritus in chronic kidney disease, an international study on pruritis in hemodialysis patients showed men were 1.1 times more likely to experience pruritus. Unlike the study conducted by Hu [8], it is said that there were no significant differences in age found between patients with pruritus and patients without itching, though they were significant.…”
Section: The Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of research conducted by Kumar [11], who identified the relationship between male sex and pruritus in chronic kidney disease, an international study on pruritis in hemodialysis patients showed men were 1.1 times more likely to experience pruritus. Unlike the study conducted by Hu [8], it is said that there were no significant differences in age found between patients with pruritus and patients without itching, though they were significant.…”
Section: The Characteristics Of Respondentsmentioning
confidence: 99%
“…Itching can cause delayed sleep and occasionally cause patients to wake up at night [19], [20]. According to Kumar's research [11], blood urea had good diagnostic values for predicting uremic-related pruritus in older people. In patients on chronic dialysis, having a man in the room, having high blood pressure, and having more serum albumin and blood sugar are all independent predictors of pruritus.…”
Section: Relationship Between Duration Of Hemodialysis and Pruritusmentioning
confidence: 99%
“…The effect of lavender aromatherapy and deep breathing exercise on … (Dwi Retnaningsih) 1403 hypertension, equilibrium syndrome, cramps, nausea, vomiting, headaches, chest discomfort, arrhythmias, itching [5], [6], fever responses, and hypoxemia [7]. Hemodialysis, which takes 12 to 15 hours of treatment time each week, is a lifelong requirement for patients with chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%